Spiritual Leadership Enhances Caring Behaviour: The Mediating Role of Calling - Sang Ayu Ketut Candrawati; Ni Kadek Ayu Sriani; Putu Gede Subhaktiyasa; Ni Komang Sukra Andini; Ni Luh Nova Dilisca Dwi Putri; Ni Ketut Citrawati; Megah Andriany (Nurse Media: Journal of Nursing, 2024)
Background: Caring behaviour is essential for patient health; however, it is often not practised optimally. Therefore, spiritually-based leadership is required to encourage this behaviour. Unfortunately, research investigating the ability of spiritual leadership to enhance caring behaviour through spiritual well-being is limited.